The effect of financial inclusion on economic and social indicators in Mexico - Guadalupe del Carmen Briano-Turrent (Latin American Journal of Central Banking (LAJCB), 2025)
This paper analyses the relationship between financial inclusion and the economic and social development in Mexico. For this quantitative research, a study sample composed by 448 observations during the 2007-2020 was analyzed using fixed effect estimations with instrumental variables 2SLS. Empirical results show that access to banking services reduces poverty, informality and inequality and favor the human development and its components of health, standard of living and education. The banking penetration decreases poverty, informality and inequality and enhances the standard of living and education. An increase in the usage of banking services diminishes the poverty and informality and increases the human development. This research contributes to practical implications for policy makers to enhance financial inclusion and human development in Mexico.
Keywords: 330; Emerging Markets; Financial inclusion; Human development; Inequality; Mexico